Virtual forums as motivational tools to build meaningful learning in times of COVID 19 - Rocky Melendez Caballero, Ciro; Flores, Edward (Seven Editora, 2023)
The development of the virtual forum in remote education in rural areas of the district of Abancay, Apurimac region, during the COVID 19 health emergency has been presented as an opportunity for students to increase not only the cultural and cognitive level, but to mobilize competencies and capabilities characterized by being timely, reflective and self-regulated. Therefore, the objective is to demonstrate the influence of the use of the virtual forum in the construction of meaningful learning The research design in the present article corresponds to descriptive research, is simple correlational and transversal. The results show that the virtual forum as a motivational tool is motivating in 53.6%, promotes interaction in 51.8% and promotes self-learning in 42.9%, while significant learning does develop communicative capacities and competences. The conclusions determine that the virtual forum stimulates communicative skills and abilities, strengthens autonomy and self-regulation skills, allows feedback and promotes cooperative work and interaction between students and teachers. DOI: 10.56238/pacfdnsv1-036